2017
DOI: 10.2147/opth.s133938
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of B-scan ultrasonography in acute fundus obscuring vitreous hemorrhage using a standardized scanning protocol and a dedicated ophthalmic ultrasonographer

Abstract: PurposeTo assess the accuracy of B-scan ultrasound (U/S) in diagnosing cases of acute fundus obscuring vitreous hemorrhage (FOVH) using a standardized scan protocol and dedicated ophthalmic ultrasonographer.MethodsConsecutive patients presenting with acute FOVH of unknown cause, between January 2013 and December 2014, were prospectively recruited. Patients underwent a scan performed by a dedicated ultrasonographer, utilizing a systematic scan sequence and using an ocular specific U/S device. The U/S findings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Multiple tears were systematically sought. Another recent study confirmed a sensitivity of 100% for the detection of rhegmatogenous retinal detachment and for the detection of new retinal tears in patients without retinal detachment [7] using a standardized scanning protocol and a dedicated ophthalmic ultrasonographer, as it was the case in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple tears were systematically sought. Another recent study confirmed a sensitivity of 100% for the detection of rhegmatogenous retinal detachment and for the detection of new retinal tears in patients without retinal detachment [7] using a standardized scanning protocol and a dedicated ophthalmic ultrasonographer, as it was the case in our study.…”
Section: Discussionsupporting
confidence: 87%
“…on 58 patients to assess the accuracy of B-scan USG for acute fundus obscuring vitreous haemorrhage (FOVH) they found that B-scan U/S scan was highly sensitive in identifying the pathology in acute FOVH. 9…”
Section: Discussionmentioning
confidence: 99%
“…In patients older than 80, the VH is more likely to be secondary to wet age-related macular degeneration (AMD) or a macroaneurysm rather than a posterior vitreous detachment (PVD). In addition to this, Sandinha et al [ 11 ] described that using a dedicated ophthalmic ultrasonographer and standardised scan protocol could significantly improve the sensitivity of identifying tears and detachments and increase the proportion of such patients who could be managed conservatively.…”
Section: Discussionmentioning
confidence: 99%